2016
DOI: 10.3174/ajnr.a4870
|View full text |Cite
|
Sign up to set email alerts
|

DTI Analysis of Presbycusis Using Voxel-Based Analysis

et al.

Abstract: BACKGROUND AND PURPOSE:Presbycusis is the most common sensory deficit in the aging population. A recent study reported using a DTI-based tractography technique to identify a lack of integrity in a portion of the auditory pathway in patients with presbycusis. The aim of our study was to investigate the white matter pathology of patients with presbycusis by using a voxel-based analysis that is highly sensitive to local intensity changes in DTI data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…Actually, this has not been tested so far although non-invasive tractography techniques like diffusion tensor imaging (DTI) are readily available in humans. However, more general DTI studies on normal aging (e.g., Salat et al, 2005 ; Giorgio et al, 2010 ; Yang et al, 2016 ) and studies on specific age-related sensory losses like presbycusis (e.g., Lutz et al, 2007 ; Profant et al, 2014 ; Ma et al, 2016 ) and glaucoma (e.g., Boucard et al, 2016 ) consistently revealed reduced subcortical and cortical white matter tracts and a decreasing fractional anisotropy (i.e., directionality of myelinated fibers) in sensory pathways of elderly humans, which may be indicative for reduced uni- and crossmodal connections.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, this has not been tested so far although non-invasive tractography techniques like diffusion tensor imaging (DTI) are readily available in humans. However, more general DTI studies on normal aging (e.g., Salat et al, 2005 ; Giorgio et al, 2010 ; Yang et al, 2016 ) and studies on specific age-related sensory losses like presbycusis (e.g., Lutz et al, 2007 ; Profant et al, 2014 ; Ma et al, 2016 ) and glaucoma (e.g., Boucard et al, 2016 ) consistently revealed reduced subcortical and cortical white matter tracts and a decreasing fractional anisotropy (i.e., directionality of myelinated fibers) in sensory pathways of elderly humans, which may be indicative for reduced uni- and crossmodal connections.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging technique has been applied to investigate the anatomical and functional alterations in the brains of patients with presbycusis (Mudar and Husain, 2016 ). Gray matter (GM) atrophy and white matter (WM) lesions, common structural abnormalities observed in previous studies, are modestly linked with presbycusis-related cognitive decline (Peelle et al, 2011 ; Eckert et al, 2012 ; Lin et al, 2014 ; Profant et al, 2014 ; Ma et al, 2016 ). Gamma-aminobutyric acid (GABA) levels in the auditory cortex, an important inhibitory neurotransmitter that can be assessed by magnetic resonance spectroscopy (MRS), were negatively correlated with the degree of age-related hearing loss (Gao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 95%
“…However, in the former study, the sample size was rather low and the statistical threshold liberal, whereas the latter study also covered congenital, noise-induced and drug-induced hearing impairments and was not restricted to an age-related decline in hearing abilities. Another DTI study identified increased diffusivity, but decreased FA in auditory areas as well as increased diffusivity in language-related areas in participants with age-related hearing loss (Ma et al 2016). Sample size was relatively low in this study as well (n = 15).…”
Section: Introductionmentioning
confidence: 60%
“…Further, (ii) grey matter volume and cortical thickness in the prefrontal cortex should be negatively associated with self-rated daily life listening effort such that with high experienced listening effort there is a thinning of cortical thickness and loss of grey matter volume (Giroud et al 2018;Rudner et al 2019;Wong et al 2010). Regarding white matter integrity, we expected (iii) decreased FA values in association tracts connecting auditory and prefrontal as well as visual areas-for instance, superior and inferior frontooccipital and longitudinal fasciculi as well as in cingulum and uncinate fasciculus-in hard-of-hearing compared to normal-hearing participants (Husain et al 2011;Luan et al 2019b;Ma et al 2016). Similarly, we hypothesized (iv) a negative association between white matter integrity in the aforementioned regions and self-rated listening effort, i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation